EVALUATION OF LIPID PROFILE COMPONENTS IN FOREIGN STUDENTS STUDYING AT THE IRKUTSK STATE MEDICAL UNIVERSITY - M. A. Darenskaya; Ya. L. Danchinova; A. Aaromal; L. I. Grebenkina; S. G. Aleksandrov; M. I. Suslikova; K. V. Sukhinina; L. I. Kolesnikova (Acta Biomedica Scientifica, 2018)
Background. A socially significant order for the training of foreign specialists, including the promotion of Russian education on the international market, certainly requires the organization of the process of students’ adaptation to the educational and information environment of the university. Particular attention deserves the components of the lipid profile, which are part of the overall adaptation syndrome.Aim: to study the features of the lipid profile in foreign students studying at the Irkutsk State Medical University.Methods. In total, 100 students of the medical profile of the Irkutsk State Medical University were enrolled in full-time study: 58 students (36 males and 22 females) were students of Russian nationality and 42 students (32 males and 11 females) – Indian students. Levels of lipid status indicators were determined with the help of Cormay kits on the automatic analyzer BTS-330 using the photometry method.Results. Hindu young men had statistically significantly higher values of triacylglycerols, very low-density lipoproteins and lower levels of high-density lipoproteins in comparison with young Russians. In the groups of girls of Indian origin, the changes concerned increased levels of triacylglycerols and very low-density lipoproteins in comparison with Russians. Gender differences were found only among Russian students – in the form of increased values of cholesterol and low-density lipoproteins in the group of girls compared to boys.Conclusion. The established functional changes in lipid metabolism in foreign students characterize the stress of the adaptive resources of the body, which, probably, can be due to the irrationality of nutrition.